Adaptation of Ochrobactrum rhizosphaerae IMV B-7956 Bacteria to the Influence of Copper (II) Chloride - Komplikevych, S.Ya.; Maslovska, O.D.; Moravska, T.I.; Yarmoliuk, I.V.; Kulishko, N.M.; Biront, N.V.; Zaritska, Y.G.; Hnatush, S.O.; Комплікевич, С.Я.; Масловська, О.Д.; Моравська, T.І.; Ярмолюк, І.В.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
In technologically altered habitats, an increased content of organic compounds, nitrogen, phosphorus, sulfur compounds, antibiotic substances, etc. is found. Therefore, microorganisms that are systematically exposed to various stressors have developed adaptation mechanisms. The strain Ochrobactrum rhizosphaerae IMV B-7956, isolated from the infiltrate lakes of the Lviv solid waste landfill, is resistant to copper, chromium, manganese, and iron in concentrations exceeding the maximum permissible concentrations. The work aimed to study the response of O. rhizosphaerae IMV B-7956 cells to CuCl2 exposure by detecting changes in the content of lipid peroxidation products, products of the oxidative modification of proteins, activity of antioxidant defense system enzymes, and synthesis of extracellular polymers. Methods. To study the effect of CuCl2 on prooxidant indicators and the activity of enzymes of the antioxidant defense system, bacteria were pre-incubated in Tris-HCl buffer containing 2–10 mM CuCl2. After one hour of incubation, the bacterial cells were washed and cultured for 1, 12, 24, and 48 h in metal-free media. The copper content in the bacterial cells was determined by atomic absorption spectrometry. The content of lipid peroxidation indicators, carbonyl groups in proteins, total low-molecular-weight thiols, enzymatic activity, and the content of exopolysaccharides and extracellular proteins were determined photometrically. Results. Within an hour, O. rhizosphaerae IMV B-7956 bacteria accumulated 2.3–7.8 mg Cu/g of biomass. Under these conditions, an increased content of lipid peroxidation products was detected. During the first hour of growth in bacterial cells, enzymes with catalase and peroxidase activity were activated. During further cultivation, an increase in the activity of other antioxidant defense enzymes was detected. Carbonyl groups in proteins are probably formed due to an increase in the content of lipid peroxidation products, as they are formed later. Within 12–48 h of growth, the copper content in the bacterial cells decreases. This leads to the restoration of growth. Conclusions. The main damaging effect of CuCl2 on bacterial cells was detected during the first 24 h of growth. Activation of the enzymes of the antioxidant system and synthesis of exopolysaccharides are among the adaptations that ensure the survival of bacteria under these conditions.